ON THE STRUCTURE OF EGIT AND EGITIM AND THEIR ENTRANCE TO TURKEY TURKISH - Balyemez, Sedat; Balyemez, Sedat (Selcuk Univ, Inst Turkish Studies, 2019)
The fact that Turkish is an additive language makes it possible to make a correct inference at first glance about which word is derived from which root. However the phonetic and semantic changes or neologisms in time can cause some coincidental similarities. In that case words that resembling each other by phonetic and semantic but actually has different stem or origin can be supposed like denominatived from the same word stem. Eg- (to bend) verb which is come to Turkey Turkish in a historical process and egit- (to educate), egitim (education) words that entered as a result of Language Revolution can be an example. In this study the process of entering egit- (to educate), egitim (education) and are not related to with the eg- (to bend) verb in term of semantic and grammatical will be clarified.
Keywords: Education; To Educate; To Bend; Word Derivation; Turkish Language Reform